PENGARUH STRATEGI PEMASARAN, E-COMMERCE, PEMAHAMAN AKUNTANSI, PENGALAMAN USAHA, DAN KREATIVITAS, TERHADAP PENINGKATAN PENDAPATAN UMKM (SURVEY PADA UMKM DI KOTA KUPANG) - .Suryaningsi, Suryaningsi; Lamaya, Fauziyah; Kiraman, Fadlul; Dian, Afra Asmici (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The aim of this research is to find out the influence of marketing strategy, e-commerce, understanding of accounting, business experience and creativity on increasing MSME income. The type of data for this research is primary data. The population in this research are MSMEs in Kupang City that are still active and registered with the Kupang City Cooperatives and UMKM Service in 2020. The number of samples determined was 200 samples. The analytical method used is multiple linear regression analysis. The research results show that E-commerce and Marketing Strategy have a significant influence on increasing MSME income. Where it is shown from the results of data processing that the significance value of the two variables is both 0.000 or greater than 0.05 from the specified standard limit. And the calculated t results for both variables are greater than the t table. Meanwhile, the variables Business Experience, Creativity and understanding of accounting have no influence on increasing MSME income. This can be shown by the results of a significance value greater than 0.005. However, simultaneously these five variables have a joint influence on increasing MSME income